Criticism Against Feminist's Thinking About Husband's and Wife’s Rights and Obligations - Faisal, Faisal; Mukri, Moh.; Asriani, Asriani (Universitas Islam Negeri Raden Intan Lampung, 2019)
Marriage is a legal place to foster a peaceful, harmonious and loving household (Sakīnah mawaddah wa rahmah). In marriage, the fulfillment of the rights and obligations of husband and wife is the main means for achieving domestic happiness. In the Islamic perspective, the husband is the head of the household and the wife is the housewife. However, in modern times, along with the emergence of feminists, the concept of the rights and obligations of husband/wife are thus re-interpreted and reconstructed on the grounds that many wives are no longer serving as housewives but also help husbands in earning a living. As a result, the aspect of equality is more prioritized than the concept of mu'āsyarah bil ma'rūf (harmonious relationship). This article examines the views of Muslim feminists about the role of husband/wife in a household, while comparing them with concepts that exist in Islamic teachings. In conclusion, the Islamic concept of the rights and obligations of wife and husband, if it is carried out consistently, will actually bring more benefit and permanence in the household than the feminist’s which is only based on the equality argument.